Vision impairment and differential access to eye health services in Aotearoa New Zealand: a scoping review - Matire Harwood; Jacqueline Ramke; Joanna Black; Himal Kandel; Jaymie Tingkham Rogers; Ben Wilkinson (BMJ Public Health)
Introduction In Aotearoa New Zealand, Māori and Pacific People experience worse health outcomes compared with other New Zealanders. No population-based eye health survey has been conducted, and eye health services do not generate routine monitoring reports, so the extent of eye health inequality is unknown. This information is required to plan equitable eye health services. In this scoping review, we aimed to summarise the nature and extent of the evidence reporting vision impairment, its main causes and access to eye health services by ethnicity in New Zealand.Methods This scoping review was reported according to Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews. An information specialist conducted a search on MEDLINE and Embase databases in October 2022. Included studies reported outcomes among any population group resident in New Zealand or attendees at New Zealand health facilities. Data screening, full-text review and data extraction were performed independently by two authors. We summarised the characteristics of studies and outcomes, and the results were synthesised narratively.Results Our search identified 2711 reports, of which 53 (from 47 studies) were included. We mapped 72 outcomes, many of which were access-related (n=32), published since 2000 (n=28) and largely focused on diabetic retinopathy (n=21) or cataract (n=13) in facility-based settings (n=18). Over two-thirds of reported outcomes were disaggregated by at least two ethnicities. When outcomes were disaggregated by ethnicity, Māori and Pacific People were consistently included, and experienced worse access and outcomes compared with other New Zealanders.Conclusion The findings of this review highlight the presence of ethnic disparity in access to diabetic retinopathy and cataract services. Closing the evidence gap identified for refractive error, glaucoma and macular degeneration service coverage could be a priority for future research. Furthermore, future research can be strengthened to enable consistent monitoring of eye health service coverage over time.